Peran Sanitasi dalam Proses Produksi dan Penyajian Makanan - Mecca, Alleyda Audia; Dalimunthe, Randy Syafaat; Ginting, Laurena; Ingtyas, Fatma Tresno (VISA: Journal of Vision and Ideas, 2025)
In daily life, we often overlook cleanliness and sanitation aspects, both in household environments and industrial settings, including food production and service. However, poor sanitation can lead to serious negative impacts, such as foodborne illnesses. Several cases of food poisoning involving pathogenic bacteria such as Salmonella, Escherichia coli, and Listeria are frequently associated with insufficient attention to sanitation in food handling. A lack of understanding or awareness about the importance of hygiene can exacerbate this situation, increasing public health risks. This study aims to examine the role of sanitation in maintaining the quality of food ingredients, the impact of sanitation implementation on food safety, and effective sanitation practices in food production and service processes. Proper sanitation at every stage of food production is crucial to prevent microbial contamination that can degrade quality and endanger consumer health. The study employs a qualitative method, using in-depth interviews with 10 culinary arts students from the 2022 cohort. The findings indicate that sanitation in production processes, such as cleaning raw materials and cooking utensils, significantly affects the quality of the food produced. Good sanitation practices can prevent cross-contamination, enhance food hygiene, and ensure safe consumption. Effective sanitation practices include thorough cleaning procedures for equipment and proper management of raw materials at every stage of production to serving. This research recommends that the food industry strengthen knowledge and implementation of sanitation practices, improve hygiene monitoring, and invest in better sanitation equipment to maintain food quality and safety.